2023
DOI: 10.1039/d3bm00835e
|View full text |Cite
|
Sign up to set email alerts
|

Matrisomal components involved in regenerative wound healing in axolotl and Acomys: implications for biomaterial development

Nancy Avila-Martinez,
Merel Gansevoort,
Juul Verbakel
et al.

Abstract: Acomys and axolotl share key regenerative components of the matrisome and glycosaminoglycan biosynthesis during scarless wound healing. Addition of key matrisomal components to biomaterials may improve skin wound healing in non-regenerating mammals.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 186 publications
(309 reference statements)
0
2
0
Order By: Relevance
“…The incredible regenerative ability of both Acomys and axolotls provides a unique opportunity for identification of ECM components which contribute to their shared regenerative capacity. A recent review compared expression of ECM-related genes between Acomys and axolotl and identified a number of shared expression patterns that may contribute to regeneration in these models, including shared upregulation of COL12A1, TNC, FN1, THBS1, THBS2, and C1QC between the two species 124 . All proteins reported as upregulated in both Acomys and axolotl display concurrent upregulation in our data, demonstrating strong agreement between our study and previous analyses.…”
Section: While Cell Markers Indicate Greater Macrophage Contribution ...mentioning
confidence: 99%
See 1 more Smart Citation
“…The incredible regenerative ability of both Acomys and axolotls provides a unique opportunity for identification of ECM components which contribute to their shared regenerative capacity. A recent review compared expression of ECM-related genes between Acomys and axolotl and identified a number of shared expression patterns that may contribute to regeneration in these models, including shared upregulation of COL12A1, TNC, FN1, THBS1, THBS2, and C1QC between the two species 124 . All proteins reported as upregulated in both Acomys and axolotl display concurrent upregulation in our data, demonstrating strong agreement between our study and previous analyses.…”
Section: While Cell Markers Indicate Greater Macrophage Contribution ...mentioning
confidence: 99%
“…All proteins reported as upregulated in both Acomys and axolotl display concurrent upregulation in our data, demonstrating strong agreement between our study and previous analyses. However, analyses incorporated into this review were limited to transcriptomics and analysis of the soluble ECM fraction 124 , limiting the conclusions that can be drawn regarding additional alterations to the insoluble, fibrillar ECM that we are able to capture in this study.…”
Section: While Cell Markers Indicate Greater Macrophage Contribution ...mentioning
confidence: 99%